Developing sustainable capacity-building in mental health research: implementation outcomes of training of trainers in systematic reviewing. Issue 1 (31st December 2020) - Jack, Helen E.; Merritt, Christopher; Medhin, Girmay; Musesengwa, Rosemary; Mafuta, Chitsanzo; Gibson, Lorna J.; Hanlon, Charlotte; Sorsdahl, Katherine; Chibanda, Dixon; Abas, Melanie
ABSTRACT: Less than 1% of biomedical research papers originate in Africa. Locally relevant mental health research, including synthesis of existing evidence, is essential for developing interventions and strengthening health systems, but institutions may lack the capacity to deliver training on systematic reviewing for publication in international journals. This paper describes the development and implementation of a training-of-trainers (ToT) course on systematic reviewing. The ToT prepared junior faculty ('trainers') from universities in Ethiopia, Malawi, and Zimbabwe to lead a five-day systematic reviewing workshop. Using an evaluation framework based on implementation science outcomes, the feasibility of the ToT was assessed by tracking the number of workshops the trainers subsequently conducted and the number of trainers and trainees who participated; acceptability was assessed through post-workshop surveys on trainee perspectives; impact was evaluated through trainee scores on a 15-item multiple choice test on systematic reviewing concepts; and sustainability was assessed based on whether the workshop was integrated into university curricula. Twelve trainers (86% of those trained) facilitated a total of seven workshops in their home countries (total 103 trainees). The first workshop run in each country was evaluated, and there was a significant improvement in mean knowledge scores between pre- and post-tests among trainees ( MD = 3.07, t = 5.90, 95% CI 2.02–4.11). In two of the three countries, there are efforts to integrate the systematic review workshop into university curricula. The cost of the workshop led by the international trainer was 1480 per participant, whereas the trainer-led workshops cost approximately 240 per participant. Overall, ToT is relatively new to research capacity building, although it has been used widely in clinical settings. Our findings suggest ToT is a promising, low-cost way to develop both technical skills of individuals and the pedagogical capacity of universities, and to promote sustainability of research capacity building programs that often have time-limited grant funding.